1992
DOI: 10.1002/elps.1150130104
|View full text |Cite
|
Sign up to set email alerts
|

A genetic factor model for the statistical analysis of multilocus DNA fingerprints

Abstract: A novel concept is described for the statistical analysis of multilocus DNA fingerprints. Utilizing this method, it is shown by simulation that the application of multilocus DNA fingerprints to paternity testing is robust against deviations from idealistic assumptions made about underlying models and parameters. Partial homozygosity, allelism and linkage at the DNA loci involved, as well as variations in estimates of band-sharing probabilities were studied for effects on the resulting paternity probabilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…But such an evaluation of x is almost impossible, because generally we neither exactly know the allele systems behind the band occurrences nor their frequencies. A recently published communication [8] outlines a model operating to some extent on the genotype level for studying and evaluating effects due to allelism, linkage, homozygosity and heterozygosity. This communication as well as some other investigations with simulated or real data pointed out that the biostatistical approaches based on the likelihood ratio or the band sharing principle are robust against violations in the HW and LE assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…But such an evaluation of x is almost impossible, because generally we neither exactly know the allele systems behind the band occurrences nor their frequencies. A recently published communication [8] outlines a model operating to some extent on the genotype level for studying and evaluating effects due to allelism, linkage, homozygosity and heterozygosity. This communication as well as some other investigations with simulated or real data pointed out that the biostatistical approaches based on the likelihood ratio or the band sharing principle are robust against violations in the HW and LE assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a positionby-position analysis of fragment sizes, Krawczak and Bockel( 1992) and Bockel et al ( 1992) showed that the problem of corn&ration may be examined by postulating "position-specific genetic factors," F, an unobservable variable. When F > 0, an individual's DNA fingerprint pattern would exhibit the presence of bands at that position.…”
Section: Discussionmentioning
confidence: 99%
“…The simulations described in the previous sections resulted in , and restriction enzyme Hinfl [6]). Thus, expected LR distributions were determined by simulation using these two figures and a mutation probability of w = 0.001, assuming independence of phenotypes at different positions as well as between mother, putative father and biological father (for details of simulations, also see [13]). In cases of true paternity, observed LR distributions are almost the same for all simulation models, as long as only half of the information is scored.…”
Section: Expected and Observed Lr Distributionsmentioning
confidence: 99%
“…Whereas a larger number of contributing loci and alleles would improve the discriminative power of the likelihood approach, genetic linkage and allelic association would detract from it. However, lack of pairwise independence of bands has already been shown to be irrelevant for decision making in paternity cases comprising trios [13].…”
Section: Simplistic Models Vs Complex Realitymentioning
confidence: 99%